Socio-Political Issues In The Songs Of “Kapital” Group Band Released In 2014-2015 - Mahardika, Moch. Dimas Galuh (Jurnal Seni Musik, 2021)
Music is an unlimited medium as a place to convey a message. Literally music is an arrangement of sounds that echo the rhythm and harmony produced from the instruments that can produce sounds. In other words music is a representation of the soul of someone who plays it. Kapital is a band from Tenggarong that performs metalcore music. The breadth of freedom of expression in music, Kapital band used music as a place to make criticisms of socio-political conditions. Kapital deliberately uses music as a medium of criticism because they realize that music lovers who listen to their work will be able to maximum capture the message if the message contained in their songs is a relevant problem with social conditions. This article, written using historical methods and the literature review approach, tried to briefly review socio-political issues in several songs released by Kapital band songs.